CONCEPTUAL STUDY ON ORGANIZATIONAL PERFORMANCE IN INDIAN CONTEXT - Gaur, Vidhu (International Journal of Psychosocial Rehabilitation, 2020)
Organizational performance is the most important dependent variable of interest for researchers working in just about any area of management. This research paper/chapter presents a review of the research that has happened in the area of organizational performance in India during the period 2003- 2015. The paper begins with a presentation on the issue of performance measurement and the associated challenges. Next, it documents research that has linked individual-level, group-level and organization-level variables to organizational performance. While presenting a description of studies, the paper also presents their critical appreciation bringing out salient points, theoretical and conceptual contributions, limitations, gaps and the scope of future research. Important areas, themes and issues that need attention are brought into focus. In the end, a multi-level model incorporating the insights gained from the survey has been presented that provides a process framework linking antecedent variables to organizational performance. The framework provides a set of working hypotheses that should set the course of future organizational performance research in the Indian context.